Translation, cross-cultural adaptation and validation of the Norwich Patellar Instability score for use in Brazilian Portuguese - Arrebola, Lucas Simões; Campos, Túlio Vinícius de Oliveira; Smith, Toby; Pereira, André Lourenço; Pinfildi, Carlos Eduardo (São Paulo Medical Journal, 2019)
BACKGROUND: The Norwich Patellar Instability (NPI) score is a tool for evaluating the impact of pa-tellofemoral instability on joint function. It has not been translated or culturally adapted for the Brazilian population before. OBJECTIVE: This study had the aims of translating and culturally adapting the NPI score for use in Brazilian Portuguese and subsequently assessing its validity for this population. DESIGN AND SETTING: Translation, cross-cultural adaptation and validation study conducted at the State Public Servants’ Institute of São Paulo, Brazil. METHODS: Sixty patients of both sexes (aged 16-40 years) with diagnoses of patellar dislocation were recruited. The translation and cultural adaptation were undertaken through translation into Brazilian Por-tuguese and back-translation to English by an independent translator. Face validity was assessed by a committee of experts and by 20 patients. Concurrent validity was assessed through comparing the Brazil-ian Portuguese NPI score with the Brazilian Portuguese versions of the Lysholm knee score and the Kujala patellofemoral disorder score among the other 40 patients. Correlation analysis between the three scores was performed using Pearson correlation coefficients with significance levels of P < 0.05. RESULTS: The Brazilian Portuguese version of the NPI score showed moderate correlation with the Brazil- ian Portuguese versions of the Lysholm score (r = -0.56; 95% confidence interval, CI: -0.74 to -0.30; P < 0.01) and Kujala score (r = -0.57; 95% CI: -0.75 to -0.31; P < 0.01). CONCLUSION: The Brazilian Portuguese version of the NPI score is a validated tool for assessing patient-re-ported patellar instability for the Brazilian population.